The Irish dairy industry – Recent history and strategy, current state and future challenges. (7th January 2020) - Kelly, Paidi; Shalloo, Laurence; Wallace, Michael; Dillon, Pat
Abstract : This study explores drivers and resulting changes in the structure and technical efficiency of Irish dairy farms from 2005 to 2018 (covering pre‐ and post‐milk quotas) during which milk production increased by 54%. Over this period, farm structure changed dramatically (fourfold increase in farmers milking >100 cows) and farmers improved technical efficiency and profitability and reduced the greenhouse gas emission intensity of milk produced. The impact of the adoption of key technologies at farm level and the contribution of strategic direction nationally (the Irish Government's Food Harvest 2020 Strategy) influencing this development are explored as are future sector challenges.